STUDI TERHADAP HADIS JIHAD ADALAH BENTUK WISATA UMAT ISLAM - Cici Febrianti; Muhammad Taufik (Adisam Publisher, 2025)
Siyahah is a kind of Muslim tourism where someone wants to go around or take a walk. Islam does not prohibit its followers from holding tours, as long as it complies with Islamic rules. Islam holds the view that traveling or traveling is an act of worship, as is found in the pillars of Islam, namely performing the Hajj which is a long journey. The main purpose of traveling in Islam is to gain knowledge and learning so that people know God better. Allah told the Prophet Muhammad to call on his people to wander the earth and explore historical places so that they could learn how to live their lives by paying attention to every process of the journey. The aim of this research is to determine the quality and understanding of the hadith of jihad as a form of Muslim tourism. It is hoped that it will bring benefits in providing knowledge and understanding of hadith so as to provide understanding to Muslims today. This research is library research, using the tahlili method to find out the meaning of the words of the hadith in depth. Understanding hadith is done by studying the textual and contextual aspects of hadith. The result of this research is the quality of the hasan hadith, this hadith provides an understanding of something better than siyahah, namely jihad fi sabilillah. The presentation of this hadith is based on Abu Daud's sharah which explains that traveling can leave congregational prayers and Friday prayers and thus run away from one's obligations to Allah SWT. Therefore, traveling or traveling does not mean that you have fought jihad in the way of Allah SWT, but those who travel by preaching and worshiping and hoping for Allah's approval are called jihad in the siyahah way.